POLITENESS STRATEGIES ANALYSIS REFLECTED IN LITTLE WOMEN MOVIE BY GRETA GERWIG - Fridolini Fridolini; Dwi Asih Arisena; Kurnia Idawati (English Education Department, 2021)
This research mostly discusses the politeness strategies that is shown in Little Women movie. Politeness is a social behaviour to a speaker towards deferent wishes of the addressee in different concerns. The purpose of this study is to find the politeness strategies and the most-frequent strategy that is used in Little Women movie. Based on Brown and Levinson (1978), there are four types of politeness strategies. Those are bald on record, positive politeness, negative politeness, and off record. Descriptive qualitative method was selected to analysed the data. The theory that are applied in this study are Brown and Levinson’s theory (1978), which concerns about the politeness strategies. The result of this term paper was shown that all of the characters use all the politeness strategies from Brown and Levinson and the most frequent strategy that is used by the characters is positive politeness. The researchers hope that this research will help the readers to get a better understanding about politeness strategies based on Brown and Levinson.